A hydrogeological assessment of the Uitenhage-Coega artesian system - Venables, Anthony John (Rhodes University, Faculty of Science, Department of Geography, 1985)
The Uitenhage artesian aquifer north-west of Port Elizabeth in South Africa, is one of the few artesian groundwater systems in Southern Africa. The Uitenhage - Coega, and Kruis River areas, are the most important portions of the Uitenhage Artesian System in terms of water abstraction and water use. This study concentrates on the Uitenhage - Coega area and in particular, on the Coega Ridge where the Table Mountain Sandstone (TNS) aquifer occurs at relatively shallow depths. The investigation is aimed at assessing the geological, hydrogeological and hydrochemical characteristics of the HIS and any other aquifers present, with the object of providing quantitative data for use in future decisions on the water resource management of the area. In order to achieve these objectives, field work, involving a hydrocensus, geological mapping, geophysical exploration, drilling, aquifer testing and hydrochemical sampling was carried out. Analysis of these data provided information on the extent of the aquifers, their hydrogeological characteristics and the chemical nature of the various groundwater types.
Keywords: Hydrogeology -- South Africa; Aquifers -- South Africa